1995
DOI: 10.1044/1058-0360.0403.05
|View full text |Cite
|
Sign up to set email alerts
|

Sounds of Zimbabwe

Abstract: The purpose of this paper is threefold. It attempts to acquaint the reader with the languages of the African country of Zimbabwe, point out the status of the profession of speechlanguage pathology in that country, and introduce a tool that has been developed to expand knowledge about the Zimbabwean child's speech development. The Sounds of Zimbabwe: Phonological Analysis and Assessment is a tool that can be used as a screening test to quickly identify a pupil's ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Both of these require a verbal response on the part of the child but generally it is only a one-word response, and they may be more suitable for assessment of complex, hard-to-depict, vocabulary. Wolf-Schein, et al (1995) developed a phonological assessment for children aged 7 and older speaking Shona or Ndebele in Zimbabwe. Naudé, Louw, and Weideman (2007) suggest using elicited conversation to examine language development of children learning English in multilingual settings in preschools in South Africa, since they have observed that children's spontaneous conversations with each other are rarely in just one language.…”
Section: Language Assessmentsmentioning
confidence: 99%
“…Both of these require a verbal response on the part of the child but generally it is only a one-word response, and they may be more suitable for assessment of complex, hard-to-depict, vocabulary. Wolf-Schein, et al (1995) developed a phonological assessment for children aged 7 and older speaking Shona or Ndebele in Zimbabwe. Naudé, Louw, and Weideman (2007) suggest using elicited conversation to examine language development of children learning English in multilingual settings in preschools in South Africa, since they have observed that children's spontaneous conversations with each other are rarely in just one language.…”
Section: Language Assessmentsmentioning
confidence: 99%
“…A lack of linguistic research about Ugandan languages means there is little information on which to base appropriate assessments and interventions. A developing service will need a research base on which to build good practice [22]. This issue is the same as in Sri Lanka where students have been integrally involved in developing language and culturally appropriate materials [19].…”
Section: Linguisticsmentioning
confidence: 99%